Continues renal replacement therapy (CRRT) with disposable hemoperfusion cartridge: A promising option for severe COVID-19. (June 2020) - Dastan, Farzaneh; Saffaei, Ali; Mortazavi, Seyed Mehdi; Jamaati, Hamidreza; Adnani, Nadia; Samiee Roudi, Sasan; Kiani, Arda; Abedini, Atefeh; Hashemian, Seyed MohammadReza
Abstract: Cytokine release syndrome is prevalent in severe cases of COVID-19. In this syndrome, an uncontrolled response of immune system occurs. Extracorporeal blood purification has been proven to effectively remove the released inflammatory cytokines. Here, we reported a successful case to represent our experience of extracorporeal blood purification in a patient with severe COVID-19.